Conceptual Model of Life Skills Transfer in Sport - Taehee Lim; Oh-Jung Kwon; Junsu Bae (Korea Institute of Sport Science, 2021)
PURPOSE This study aimed to develop a model for life skills transfer in sport. METHODS A literature review of research on life skills transfer was conducted. The prior representative studies on sport life skills and transfer models were selected and discussed to improve the validity of this study. RESULTS First, based on the basic psychological needs of the internalization and generalization of life skills, the model for life skills transfer should consider the influence of the explicit and implicit climate and environment. Furthermore, access to cognitive processes is required based on the conceptualization and integration of transfer. Second, the concept of a transfer was defined, and key issues of the cognitive processes that support the connection between the sport domain and out of the sport domain were discussed. Third, the model for life skills transfer in sport was presented. In this model, life skills transfer occur through sport context, cognitive process, promoting factors, and out of sport context. CONCLUSIONS Since the 2000s, research on life skills and transfer in sport has developed quantitatively based on positive youth development theory. Unfortunately, research on this area in South Korea is very insufficient. This study suggests a model for life skills transfer in sport based on an extensive and systematic analysis of the prior research, and this model can be used for future research.